Pengaruh Fitur Live Streaming E-Commerce terhadap Niat Beli Konsumen Pada UMKM Di Indonesia : Tinjauan Literatur Sistematis - Pramesti, Prita; Aminah, Mimin; Johan, Irni Rahmayani; Sinaini, La (Institut Pertanian Bogor, 2025)
As online shopping trends and competition in the e-commerce sector continue to grow, live streaming has emerged as a promising interactive marketing strategy. This study examines the influence of e-commerce live streaming features on consumer purchase intention through a systematic literature review, analyzing 30 articles published between 2022 and 2024. The objectives of this research are to summarize existing data on the impact of live streaming features on purchase intention, identify the factors influencing the relationship between live streaming and purchase intention, and provide recommendations for Indonesian MSMEs to optimize the use of live streaming. Findings show that China is the dominant research location, with agricultural products being the most frequently studied category. Most studies employed a quantitative approach, particularly using Structural Equation Modeling (SEM). The analysis identified 130 factors affecting consumer purchase intention, which were categorized into ten main themes. Based on these findings, this study recommends that Indonesian MSMEs optimize live streaming by strengthening emotional aspects such as affective trust and psychological distance, as well as leveraging influencer credibility to attract more consumers. In addition, service quality, information quality, and social presence during live streaming sessions play a crucial role in enhancing consumer satisfaction and purchase intention. This study is expected to serve as a strategic reference for MSMEs in maximizing the potential of live streaming as an effective digital marketing tool.